Inflammatory cytokine and microRNA responses of primary human dendritic cells cultured with Helicobacter pylori strains - Hocès De La Guardia, Anaïs; Staedel, Cathy; Kaafarany, Itidal; Clément, Aurélien; Roubaud, Claire; Mégraud, Francis; LEHOURS, PHILIPPE (Frontiers in Microbiology, 2013)
Primary human dendritic cells (DC) were used to explore the inflammatory effectors, including cytokines and microRNAs, regulated by Helicobacter pylori. In a 48 h ex-vivo co-culture system, both H. pylori B38 and B45 strains activated human DCs and promoted a strong inflammatory response characterized by the early production of pro-inflammatory TNF and IL-6 cytokines, followed by IL-10, IL-1ß and IL-23 secretion. IL-23 was the only cytokine dependent on the cag pathogenicity island status of the bacterial strains. DC activation and cytokine production were accompanied by an early miR-146a upregulation followed by a strong miR-155 induction, which mainly controlled TNFα production. These results pave the way for further investigations into the nature of H. pylori antigens and the subsequently activated signaling pathways involved in the inflammatory response to H. pylori infection, the deregulation of which may likely contribute to gastric lymphomagenesis.